A Study on Rural Customer Attitude towards Green Marketing - Celin Difna C A; Dr. Princy Francis (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Businesses need to constantly assess the latest and most attractive marketing trends. People have begun to be developing more awareness and perception about environment friendly products, which Initiate a trend concept of green marketing used by the companies as their strategies to earn profit and also protect the environment. This increased concern towards society has given rise to purchase and consumption of green products. Although a variety of research on green marketing has been conducted across the globe; little academic research on rural consumer perception and preferences has been carried out in India. In this study we try to explore the factors affecting the purchase decision of green products and also tries to analyze the relationship between green marketing practices and purchase decision. Both primary and secondary data were used for this study. The questionnaire was designed to know the rural consumers’ green product satisfaction level,factors affecting purchase decisions and to understand the relationship between green marketing strategies and purchase behavior.. The consumers were selected through convenience sampling technique and the sample size considered for the study is 100 respondents. The collected data were analyzed using a statistical package for social science (SPSS ).The statistical tools used for this study are t-test, correlation, ANOVA ,mean and Standard deviation. The results shows a positive relationship between green marketing practices and purchase decision.